THE INFLUENCE OF LOAN TO DEPOSIT RATIO AND CAPITAL ADEQUACY RATIO ON NON PERFORMING LOANS AT PT. WEST JAVA REGIONAL DEVELOPMENT BANK, Tbk. - sartika, andi; Salam, Safaruddin (Universitas Ichsan Sidenreng Rappang, 2023)
This research aims to determine the effect of Loan To Deposit Ratio and Capital Adequacy Ratio on Non-Performing Loans at PT. West Java Regional Government Bank, Tbk. The type of data used is a quantitative data model. The data source used is secondary data. The analytical methods used are descriptive quantitative, multiple linear regression, correlation coefficient (R), coefficient of determination (R2), F test and t test. The research results show the value of the regression equation Y = 14.3929 + 0.00029X1 - 0.7005X2. The t b1 test shows that the Loan To Deposit Ratio has a positive but not significant effect on Non Performing Loans and the b2 t test shows that the Capital Adequacy Ratio has a negative and significant effect on Non Performing Loans. The F test results show that the Loan To Deposit Ratio and Capital Adequacy Ratio have a simultaneous and significant effect on Non-Performing Loans at PT. West Java Development Bank, Tbk. Hyoptheses H2 and H3 are accepted but hypothesis H1 is rejected.